Cohesive Growth in Europe: A Tale of Two Peripheries - Michael Dauderstädt (Intereconomics)
Abstract Over the last two decades, income disparities between EU member states tended to decline, particularly before the financial crisis. While Central and Eastern Europe caught up with the EU average, Southern Europe fell behind after 2009. Catch-up growth in both peripheries relied on nominal convergence (real appreciation) and foreign capital. Further growth can and should be fostered by an economic policy that does not neglect domestic demand, stabilises capital markets and invests in research, education, health and intangibles.